Synthesis of Biologically Active Gibberellins and Surface-Active Substances by Nocardia vaccinii IMV B-7405 in the Presence of Erythritol - Pirog, T.P.; Leonova, N.O.; Piatetska, D.V.; Shevchuk, T.A.; Пирог, Т.П.; Леонова, Н.О.; П’ятецька, Д.В.; Шевчук, Т.А. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
A promising direction today is the creation of integrated technologies for obtaining complex microbial preparations for crop production. The ability of Nocardia vaccinii IMV B-7405 to simultaneously synthesize surfactants with antimicrobial activity and stimulating phytohormones (auxins, cytokines, gibberellins) was previously established. However, the concentration of synthesized gibberellins was low. One of the approaches to the intensification of the target metabolites synthesis is the introduction of a precursor of their biosynthesis into the cultivation medium. Since in most bacteria gibberellins are formed in the methyl-erythritol-4-phosphate pathway, it was assumed that erythritol could be the precursor of the synthesis of these phytohormones. In addition, surfactants are secondary metabolites, the biological activity of which can vary depending on the cultivation conditions. The aim of the work is to investigate the possibility of increasing the synthesis of gibberellic phytohormones by the surfactant producer N. vaccinii IMV B-7405 in the presence of exogenous erythritol in the culture medium and to determine the effect of erythritol on the biological properties of surfactants synthesized under such conditions. Methods. Cultivation of N. vaccinii IMV B-7405 was carried out in a medium with refined or waste oil (2%, volume fraction) containing 100–500 mg/L erythritol. The concentration of gibberellins was determined by the method of high-performance liquid chromatography, while the concentration of surfactants - by the weight method after extraction and modification with a mixture of chloroform and methanol. The antimicrobial activity of surfactants against phytopathogenic bacteria was analyzed by the indicator of the minimum inhibitory concentration, and the degree of destruction of biofilms – by the spectrophotometric method. Results. It was established that the introduction of 300–400 mg/L erythritol into the culture medium of N. vaccinii IMV B-7405 was accompanied by the 2–14 times increase in the concentration of biologically active gibberellins GA3 and GA4 compared to the indicators of synthesis in the medium without the precursor. Data on the formation of gibberellins by N. vaccinii IMV B-7405 were correlated with the activity of one of the key enzymes of their biosynthesis: in the presence of erythritol, the activity of 2-C-methyl-D-erythritol-4-phosphate-cytidyltransferase was 3–12 times higher than in cells of the IMV B-7405 strain grown without a precursor. In the presence of erythritol, the formation of surfactants with high antimicrobial activity against phytopathogenic bacteria and the ability to destroy their biofilms were observed. The minimum inhibitory concentrations of surfactants synthesized by the addition of erythritol at the end of the exponential growth phase of the IMV B-7405 strain on waste oil for the pathogens of tomato bacteriosis were 0.8–25 μg/mL, that is, lower than the indicators established for surfactants formed without erythritol (3.13−100 μg/mL). Destruction of biofilms of phytopathogenic bacteria under the influence of surfactants obtained in the presence of erythritol in a medium with waste oil was 8–34% higher compared to destruction under the action of surface-active substances synthesized without this precursor. It was established that the introduction of erythritol into the culture medium of N. vaccinii IMV B-7405 was accompanied by a twofold increase in the activity of NADP+-dependent glutamate dehydrogenase (the key enzyme in the biosynthesis of aminolipids responsible for the antimicrobial activity of the surfactant complex). Conclusions. The obtained results are the basis for the development of a highly efficient integrated technology of biosynthesis of surface-active substances and phytohormones for crop production. The complex bacterial preparation can be used both to stimulate the growth of agricultural plants and to control the number of pathogens of their bacteriosis.